2013
DOI: 10.1007/s10552-013-0188-y
|View full text |Cite
|
Sign up to set email alerts
|

Childhood leukemia and lymphoma: time trends and factors affecting survival in five Southern and Eastern European Cancer Registries

Abstract: The favorable mortality trends highlight the progress in Southern-Eastern European countries along their trajectory to converge with Northern-Western EU counterpart states. Socioeconomic status may act as a multipotent factor underlying the study findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 26 publications
2
25
2
Order By: Relevance
“…A study from Australia, a country with vast areas of very low density population, reported better survival rates for all childhood cancers and specifically leukaemia for children living in major cities compared to those living elsewhere . Living in rural areas was also associated with less favourable prognosis in recent multi‐national findings from Bulgaria, Turkey and Russia for survival from leukaemia as well as from lymphoma . However, in Denmark four specialised paediatric clinics cover the entire country, with relatively short distances to the treating centre from most places in Denmark and highly standardised treatment irrespective of the treating hospital.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Australia, a country with vast areas of very low density population, reported better survival rates for all childhood cancers and specifically leukaemia for children living in major cities compared to those living elsewhere . Living in rural areas was also associated with less favourable prognosis in recent multi‐national findings from Bulgaria, Turkey and Russia for survival from leukaemia as well as from lymphoma . However, in Denmark four specialised paediatric clinics cover the entire country, with relatively short distances to the treating centre from most places in Denmark and highly standardised treatment irrespective of the treating hospital.…”
Section: Discussionmentioning
confidence: 99%
“…This gap increases with the enlargement of the definition of Europe. Many registries however contributed to international studies of incidence and survival dedicated specifically to childhood cancer [70,71] and data from new areas emerge [72]. Registries with more expertise often offer help to the developing ones through 'twinning' activities, such as hosting collaborators from Hungarian childhood registry by the UK's NRCT or consultations provided by Germany to the registry in the Moscow region.…”
Section: Discussionmentioning
confidence: 99%
“…In Greece, the time trend similarly increased on average by 0.99% annually [95% confidence interval (CI): 0.03-2.60] during the period 1996-2013 (Petridou et al, 2013;NARECHEM-BT, 2014). Similarly, during the same period, CD has gained popularity in the developed world, with rates well above the 15% recommended by WHO (Gibbons et al, 2010).…”
Section: Introductionmentioning
confidence: 99%